2015
DOI: 10.1080/02640414.2014.1003585
|View full text |Cite
|
Sign up to set email alerts
|

Perform kicking with or without jumping: joint coordination and kinetic differences between Taekwondo back kicks and jumping back kicks

Abstract: We investigated joint coordination differences between Taekwondo back kicks and jumping back kicks, and how jumping (in performing the latter) would alter engaging ground reaction forces (GRF) in executing kicking. Ten skilful athletes volunteered to perform both kinds of kicking within the shortest time for three successful trials. Three high-speed cameras and two force platforms were used for data collection, and the trial with the shortest execution time was selected for analysis. Movements were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This is in line with previous studies (Kazemi et al, 2014) that highlighted that males use attacking actions to score one point (SC1), which contrasts with obtaining a point after a dodge, since the sequence is ended and a new sequence starts (with an attack). Other studies have pointed out the advantage of using the longer time needed to carry out a spin (Cheng et al, 2015; López-López et al, 2015) as compared to linear or circular kicks (Serina and Lieu, 1991). Actions with the back leg may possible unbalance the opponent (González, 2011) and have greater impact force (Pieter and Pieter, 1995; Pêdzich et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies (Kazemi et al, 2014) that highlighted that males use attacking actions to score one point (SC1), which contrasts with obtaining a point after a dodge, since the sequence is ended and a new sequence starts (with an attack). Other studies have pointed out the advantage of using the longer time needed to carry out a spin (Cheng et al, 2015; López-López et al, 2015) as compared to linear or circular kicks (Serina and Lieu, 1991). Actions with the back leg may possible unbalance the opponent (González, 2011) and have greater impact force (Pieter and Pieter, 1995; Pêdzich et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study identified in this review specifically explored effective mass and its relationship to kicking strikes, reporting on the magnitudes to which effective mass contributed to front, side, and roundhouse kicks [ 107 ]. The amount of effective mass involved in a strike is suggested to depend on an athlete’s skill level, with skilled athletes able to time stiffening of the striking limb to occur on or immediately before impact, thereby increasing effective mass and subsequent impact force [ 97 , 107 ]. The neuromuscular action believed to create this stiffening has been referred to as a “contraction-relaxation-contraction strategy” [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the start of the doubleleg attack begun at the moment vertical velocity of the COM exceeded −0.1 m/s (negative to represent downward velocity). Previous research on Taekwondo kicking and rugby tackling defined the end of the attack as the moment of contact (Cheng et al, 2015;Kawasaki et al, 2018) ADDIN EN.CITE. We defined the timing when the horizontal acceleration of the defender's contralateral greater trochanter marker exceeded 10 m/s 2 because an ipsilateral marker was often hidden by the attacker.…”
Section: Data Collectionmentioning
confidence: 99%